Dynamic Load Modulation Scheme for Digital Transmitters - Diogo Rafael da Silva Santos (2018)
The design of a Dynamic matching network topology, using the Particle Swarm Optimization (PSO) method is proposed in this dissertation. The resulting matching network should have three distinct impedance values (10Ohm 20Ohm and 30Ohm, the same current phase in the antenna and an high intrinsic efficiency. Preliminary results were tested and validated on the Cadence Virtuoso simulator with BSIM models and in a latter stage also real verification is performed.